Functional outcomes of microdiscectomy in Bertolotti syndrome: the relationship between lumbosacral transitional vertebrae and lumbar disc herniation: a prospective study in Greece - Stylianos Kapetanakis; Krikor Gkoumousian; Nikolaos Gkantsinikoudis; Constantinos Chaniotakis (Asian Spine Journal)
Study Design The lumbosacral transitional vertebrae (LSTV) in patients with Bertolotti syndrome (BS) cause alterations in the biomechanics of the lumbosacral junction. These entities have been associated with secondary conditions, such as lumbar disc herniation (LDH). Purpose To investigate the clinical outcomes of microdiscectomy in patients with symptomatic LDH and BS. Overview of Literature There is limited data in the literature on the functional outcomes of patients with LSTV who undergo microdiscectomy. Methods This study enrolled 308 patients diagnosed with LDH and concurrent LSTV. All patients underwent microdiscectomy. Clinical evaluation was performed preoperatively and at distinct follow-up intervals of 1, 3, 6, and 12 months, and 2 and 5 years postoperatively. Assessment included clinical examination and implementation of the well-established, patient-reported outcome measures Visual Analog Scale (VAS) and Short-Form 36 (SF-36) Medical Health Survey Questionnaire for Health-Related Quality of Life (HRQoL) analysis. Furthermore, the anatomical relationship between LSTV and LDH was also studied. Results The SF-36 indices and VAS score were statistically significantly ameliorated within the follow-up period. Maximum improvement was noted at 3 months, with further minimal improvement after 6 months, and stabilization of indices until the end of follow-up. Castellvi type IB was the most frequent LSTV type. The adjacent level (L4–L5) just above the LSTV was the most affected with an incidence of 72.1%. In the subgroups of Castellvi type IA, IIA, and IIIA, the LDH side was ipsilateral with the LSTV in 38.3% of patients. In this study, all patients underwent microdiscectomy and demonstrated favorable clinical outcomes (functional recovery and pain relief) and notable amelioration of HRQoL. Conclusions To the best of our knowledge, this is the first study to conduct a holistic assessment in an attempt to delineate the impact of LSTV presence on the postoperative HRQoL of these individuals.